2015
DOI: 10.1001/jamaneurol.2014.4144
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Trial of Flutemetamol Labeled With Radioactive Fluorine 18 Imaging and Neuritic Plaque Density

Abstract: In vivo imaging of brain β-amyloid, a hallmark of Alzheimer disease, may assist in the clinical assessment of suspected Alzheimer disease. OBJECTIVE To determine the sensitivity and specificity of positron emission tomography imaging with flutemetamol injection labeled with radioactive fluorine 18 to detect β-amyloid in the brain using neuropathologically determined neuritic plaque levels as the standard of truth. DESIGN, SETTING, AND PARTICIPANTS Open-label multicenter imaging study that took place at dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
229
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(238 citation statements)
references
References 30 publications
6
229
2
1
Order By: Relevance
“…PET imaging ligands including Pittsburgh compound B ( 11 C-PIB) [2], 18 F-florbetaben [3], 18 F-flutemetamol [4] and 18 F-florbetapir [5] have been developed for estimation of cortical beta amyloid (Aβ) neuritic plaque deposition, a hallmark pathology, and a required element for the evaluation of neuropathological changes in patients with Alzheimer's disease (AD) [6]. As shown by their respective package inserts/summaries of product characteristics, as well as the published literature [7][8][9], reader accuracy in the pivotal trials for the 18 F-labeled agents averaged close to 90% for discriminating patients found at autopsy to have no or sparse neuritic plaques (amyloid-negative, Aβ−) from those found to have moderate to frequent plaques (amyloid-positive, Aβ+). However, as might be expected, within each of these development programs, there were individual readers with sensitivity or specificity values below the average, and in some with values below 80%.…”
Section: Introductionmentioning
confidence: 99%
“…PET imaging ligands including Pittsburgh compound B ( 11 C-PIB) [2], 18 F-florbetaben [3], 18 F-flutemetamol [4] and 18 F-florbetapir [5] have been developed for estimation of cortical beta amyloid (Aβ) neuritic plaque deposition, a hallmark pathology, and a required element for the evaluation of neuropathological changes in patients with Alzheimer's disease (AD) [6]. As shown by their respective package inserts/summaries of product characteristics, as well as the published literature [7][8][9], reader accuracy in the pivotal trials for the 18 F-labeled agents averaged close to 90% for discriminating patients found at autopsy to have no or sparse neuritic plaques (amyloid-negative, Aβ−) from those found to have moderate to frequent plaques (amyloid-positive, Aβ+). However, as might be expected, within each of these development programs, there were individual readers with sensitivity or specificity values below the average, and in some with values below 80%.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of positron emission tomography (PET) imaging agents such as Pittsburgh compound B [5], 18 F-florbetaben [6], 18 F-flutemetamol [7], and florbetapir F 18 [8,9], which bind to fibrillar β-amyloid (Aβ), has made it possible to estimate, in living patients, the density of neuritic amyloid plaques [10,11,12,13,14]. Because neuritic plaques are a required component of a pathological diagnosis of AD, PET-derived information regarding neuritic plaque density could be of value in the diagnosis of patients with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 false-negative cases became positive when CT was used to help with the anatomic details. The remaining 2 false-negative cases were borderline [32]. An additional study aimed to determine the ability of flutemetamol to detect amyloid by PET imaging in different phases of amyloid deposition and found that this approach detects a positive signal in advanced phases of amyloid deposition (phase [4][5].…”
Section: [ 18 F]3'-f-pib or Flutemetamolmentioning
confidence: 99%